Type the correct answer in each box. Use numerals instead of words. It hecessary, use
Find the factors of function f, and use them to complete this statement.
(6) = 224 - 29 - 1832 + 99
From left to right, function fhas zeros at I =
and I

Type the correct answer in each box Use numerals instead of words It hecessary use Find the factors of function f and use them to complete this statement 6 224 class=

Respuesta :

s1m1

Answer:

Step-by-step explanation:

you can start by factoring x

x(2x³-x²-18x+9)

you can group terms in parentheses strategicly

x(2x³-18x-x²+9)=x[2x(x²-9)-(x²-9)]

now we can factor x²-9

x(x²-9)(2x-1)

factor the diference of two squares x²-9=x²-3²

x(x-3)(x+3)(2x-1)

so the roots are found by using the zero product rule

x(x-3)(x+3)(2x-1)=0 will give

x=0, x-3=0 so x=3, x+3=0 so x=-3, 2x-1=0 so x=1/2

from left to right

-3, 0, 1/2, 3

Answer:

1. -3

2. 0

3. 1/2

4. 3

Step-by-step explanation:

ACCESS MORE